The Influence of Career Development on Employee Performance with Training as an Intervening Variable at the North Sumatra Culture and Tourism Service - Khairunnisah Khairunnisah; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2024)
This research was conducted to determine the effect of career development on employee performance with training as an intervening variable at the North Sumatra Culture and Tourism Service by conducting a path analysis research method, this type of research uses quantitative, and the source of this research uses primary data sources. This research collects data by means of distributed questionnaires, the population used was 119 employees and a sample was drawn using the Slovin formula to become 92 employees. The results of this research are as follows: Training has a positive and significant influence on employee performance with the original sample being 0.316 and P values 0.035 < 0.05 meaning hypothesis accepted. Career Development has a positive and significant effect on Employee Performance with an original sample value of 0.621 and a P value of 0.000 < 0.05, meaning the hypothesis is accepted. Career Development has a positive and significant effect on Training with an original sample value of 0.933 and ap value of 0.000 <0.05, meaning the hypothesis can be accepted. Career development has a positive and significant effect on employee performance indirectly through training with an original sample value of 0.294 and a P value of 0.032 < 0.05, the hypothesis can be accepted.